Knowledge and Attitude of Medical Students toward Plastic Surgery - Gathariki, Mukami; Ajujo, Martin; Odiero, Lucianne; Amuti, Thomas (Journal of Health and Allied Sciences NU, 2020)
Introduction Inadequate professional and medical exposure and misconceptions about plastic surgery have not only been linked to students’ poor knowledge and attitude toward it, but also bias against the selection of plastic surgery as a specialty. This assertion is yet to be tested and confirmed in our setting. This study therefore aimed to determine the knowledge and attitude of medical students toward plastic surgery.Methods One hundred and eight (108) students between their 3rd and 4th year of study were randomly recruited and handed structured questionnaires on knowledge and attitude toward plastic surgery. Data were then analyzed using SPSS and represented in percentages, medians, and means. Mann-Whitney and Kruskal–Wallis tests were done to assess for significant statistical differences based on gender grouping and year of study, respectively. A p-value ≤ 0.05 was considered significant at a 95% confidence interval.Results Majority of the students had some awareness about plastic surgery since, a majority (88%) identified plastic surgery with cosmetics and identified trauma as the main condition handled by plastic surgeons. Sixty-four percent (64%) acknowledged the risks associated with plastic surgery and 79.6% noted the presence of the procedures in Kenya. When assessing attitude, 62% reported that they did not want to pursue plastic surgery in the future, 75% would not consider plastic surgery done on them and 77% of the respondents felt embarrassed to undergo the surgery if their family knew while another 77% felt embarrassed if their friends knew. It is worth noting that 55% had their initial exposure to plastic surgery through information from the media sources. Mann-Whitney test done to assess for gender differences only revealed significant difference (p-value = 0.009) on assessing for the availability of plastic surgery procedures in Kenya. Kruskal–Wallis test did not reveal any significant differences based on year of study.Conclusion Data from our study suggest that students have some awareness about plastic surgery but have a poor attitude toward it.
Keywords: plastic surgery; cosmetics; medical students